Éducation routière : au risque de la norme - Marc Camiolo (Université de Provence, 2013)
In this article, we wish to question the role of the driver training in France as it transmits a risk culture by the media of the driving standards, when its mission is the "road safety" and the "safe driver training". In this purpose, we studied the practices of the driver's education and, in particular road accident that happen during courses. This research is framed by the debates around the Society of risk (Beck, 2001) and the concept of the "counter production of modern institutions" (Illich, 2005), as well as the theory of risk homeostasis (Wilde, 2001). The accidents analysis has been done in the frame of the training of experimented driving teachers with La méthode d'analyse en groupe (Chaumont et al., 2005). We present in details a case which implied four half-directed interviews and a topologic analysis with the teacher implicated in this accident.